Local Delivery Is Critical for Monocyte Chemotactic Protein-1 Mediated Site-Specific Murine Aneurysm Healing - Hourani, Siham; Motwani, Kartik; Wajima, Daisuke; Fazal, Hanain; Jones, Chad H.; Doré, Sylvain; Hosaka, Koji; Hoh, Brian L. (Frontiers in Neurology, 2018)
Background Local delivery of monocyte chemotactic protein-1 (MCP-1/CCL2) via our drug-eluting coil has been shown to promote intrasaccular aneurysm healing via an inflammatory pathway. Objective In this study, we validate the importance of local MCP-1 in murine aneurysm healing. Whether systemic, rather than local, MCP-1 delivery can direct site-specific aneurysm healing has significant translational implications. Demonstrating efficacy of systemic MCP-1 would allow for aneurysm treatment by a pill rather than endovascular procedure. Furthermore, we confirm that MCP-1 is the primary effector in our MCP-1 eluting coil-mediated murine aneurysm healing model. Methods We compare aneurysm healing with repeated intraperitoneal MCP-1 versus vehicle injection, in animals with control poly-DL-lactic glycolic acid (PLGA)-coated coils, to investigate systemic effect of MCP-1. We further evaluate the MCP-1-associated tissue healing response by systemic knockout and selective inhibition of MCP-1 or CCR2 (MCP-1 receptor) to investigate local effect of MCP-1. Using immunofluorescent probing, we explore cell populations found in healed aneurysm tissue following each intervention. Results Systemically administered MCP-1 with PLGA coil control does not produce comparable aneurysm healing, as with MCP-1 eluting coils. MCP-1-directed aneurysm healing is eliminated by selective inhibition of MCP-1 or CCR2 and in MCP-1-deficient or CCR2-deficient mice. With systemic administration, no difference in cell types was observed, whereas myofibroblast and M2 macrophage staining were attenuated by MCP-1/CCR2 blockade or deficiency. Conclusions We show that systemic MCP-1 concurrent with PLGA-coated platinum coil implant is insufficient to produce site-specific aneurysm healing. MCP-1 is a critical, not merely complementary, actor in the aneurysm healing pathway.